2008
DOI: 10.1007/s00268-008-9576-y
|View full text |Cite
|
Sign up to set email alerts
|

Acute Care Surgery: A New Training and Practice Model in the United States

Abstract: The specialty of trauma is at a crossroads. Choosing a career in trauma is associated with concerns related to lifestyle issues and maintenance of adequate operative experience. Trauma and critical care surgeons in the U.S. have reexamined their role based on these concerns and the realization that surgeon resources for the injured patient are in jeopardy. After much work over the past five years, a model of "Acute Care Surgery" has emerged and a training curriculum has been proposed. This article reviews the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 28 publications
0
35
0
Order By: Relevance
“…6 In such instances, establishing an ACS service entailed either re-expansion of the trauma surgeon's clinical and operative domain 7,8 or the creation of an emergency surgery service that excluded care of trauma patients. 9 In large community hospitals that do not serve as trauma centres, surgical hospitalist practices are emerging to meet the hospitals' emergency surgery coverage needs. These later models tend not to include surgical critical care.…”
Section: Discussionmentioning
confidence: 99%
“…6 In such instances, establishing an ACS service entailed either re-expansion of the trauma surgeon's clinical and operative domain 7,8 or the creation of an emergency surgery service that excluded care of trauma patients. 9 In large community hospitals that do not serve as trauma centres, surgical hospitalist practices are emerging to meet the hospitals' emergency surgery coverage needs. These later models tend not to include surgical critical care.…”
Section: Discussionmentioning
confidence: 99%
“…(3) In response, numerous accomplishments were achieved; these included changes in prehospital care and paramedic training, development of emergency management systems and standardised approaches to trauma patients, which are now commonplace worldwide. (4) A landmark study showed that the consequence of such system development in Level I trauma centres is a significant reduction in trauma-related mortality. (5) However, the last 15 years have seen the rise of new challenges that put the future of trauma surgery in question.…”
Section: The Evolution Of Acute Care Surgerymentioning
confidence: 99%
“…(9,10) ACS needed to address the impending crisis, be viable and produce an attractive lifestyle. (4) The product of this vision, 'the acute care surgeon', is a subspecialist in the provision of ESAT and critical care. This American model of care has reinvigorated the management of ESAT patients.…”
Section: The Evolution Of Acute Care Surgerymentioning
confidence: 99%
“…Hoyt et al in 2008 point out that trainees themselves question the integrity of the training system with 'concerns of maintenance of adequate operative experience'. 8 Leadership within the trauma community has recognized these concerns over the last two decades and spearheaded the development of parallel programs to enhance training. Certainly, the concern and effort is real.…”
Section: Introductionmentioning
confidence: 99%